2022
DOI: 10.1007/s40200-022-01080-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of high frequency ultrasound score (DCEC) in diabetic peripheral neuropathy

Abstract: Objectives To summarize the ultrasonic characteristics of peripheral nerve damage in type 2 diabetes and to verify the diagnostic value of DCEC score for DPN. Methods A total of 289 patients with type 2 diabetes evaluated peripheral neuropathy with neuroultrasound and nerve conduction at the Affiliated Hospital of Guizhou Medical University from June 2016 to June 2020. According to the diagnostic criteria from 2017 guidelines of China, 289 patients with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…By observing indicators such as the longitudinal diameter, width, and depth of the subcutaneous fat layer, doctors can have a more comprehensive understanding of lipohypertrophy. 16 This quantitative data provides a more scientific basis for formulating individualized treatment plans, assisting in timely adjustments of insulin injection sites, and reducing the risk of complications. When comparing the detection rates and the number of detected sites between the two groups, the research group demonstrated a more pronounced advantage.…”
Section: Discussionmentioning
confidence: 99%
“…By observing indicators such as the longitudinal diameter, width, and depth of the subcutaneous fat layer, doctors can have a more comprehensive understanding of lipohypertrophy. 16 This quantitative data provides a more scientific basis for formulating individualized treatment plans, assisting in timely adjustments of insulin injection sites, and reducing the risk of complications. When comparing the detection rates and the number of detected sites between the two groups, the research group demonstrated a more pronounced advantage.…”
Section: Discussionmentioning
confidence: 99%